Microwave breakdown in an overmoded relativistic backward wave oscillator operating at low magnetic field. (20th April 2021) - Xiao, Renzhen; Gui, Youyou; Zhang, Guangshuai; Shi, Yanchao; Wang, Huida; Chen, Kun
Abstract: Microwave breakdown has always been a huge challenge to the development of high-power microwave (HPM) sources. Some unique breakdown phenomena in a novel and powerful overmoded relativistic backward wave oscillator (RBWO) operating at low magnetic field are demonstrated. Three different breakdown mechanisms are utilized to explain these phenomena through detailed electromagnetic field calculation and particle-in-cell demonstration and effective methods are applied or suggested to mitigate the breakdown. The breakdown in the slow wave structure (SWS) mainly results from bombardment by the main electron beam under the intense radial electric field. Increasing the span between the main electron beam and the SWS or applying a coaxial extraction structure operating at coaxial TM01 mode might decrease the radial electric field and lessen the bombardment. The breakdown in the internal reflector originates with the field-induced emission in the inner ring under the intense axial electric field of the TM01 and TM02 mode and the subsequent electron-triggered emission in the outer ring. Removing the central part or constructing a complex reflector surface can suppress the emission. The breakdown in the slot retained for the Rogowski coil results from low pressure gas discharge initiated by microwave leakage from the RBWO into the diode region. Pasting microwave absorbing material into the coaxial diode region helps to obtain normal beam current waveforms measured by the Rogowski coil.